Artes plásticas y su impacto en la creatividad en los estudiantes de educación inicial en la Unidad Educativa Francisco Huerta Rendón - Gómez Cervantes, Caitlan Nathaly (2023)
The use of plastic arts in initial education generates great benefits for the development of creativity in children, the case study is carried out in the Francisco Huerta Rendon Educational Unit, in which it is observed as problematic in the student's lack of goals and objectives. which is one of the consequences of the lack of development of creativity, due to the fact that the implementation of activities with plastic arts is scarce, therefore the present case study aims to analyze the theoretical impact of plastic arts on the creativity of Initial education students in the Francisco Huerta Rendón educational unit, to achieve the objective it was necessary to meet the following specific objectives, to know the plastic arts activities that stimulate creativity in students, to identify the levels of creativity according to age of the students, select the types of plastic arts that generate novel ideas in the students before. To carry out this case it was necessary to use the following methodology; descriptive method, analytical method, non-experimental design, in addition to using techniques such as sample for convenience, observation and survey, the results of the case are based on the response trend that the sample of the population determines in the survey that was developed from of the dimensions of the theoretical framework, concluding that the institution has a weakness and it is recommended to implement more activities with plastic arts, since it is observed in the students disinterest, demotivation and difficulties to devise novel alternatives to conflicts.